KOMUNIKASI KEBIJAKAN DALAM PELAKSANAAN DANA DESA DI DESA WATUDAMBO II KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - WUMU, ABDUL MUNIF; DENGO, SALMIN; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study is to find out how policy communications in village funding in the Desa WatudamboII district north Minahasa district.Research uses a descriptive - qualitative approach. The policy is based onthree key aspects of public policy communication, of transmission, clarity and consistency. The researchinformant is the village chief and village device, the chairman and member of the village council, the chairmanof the village PKK, the group representative, and the village public figure, a total of 8 informers. Datacollection uses the interview guidelines, while the analysis techniques used are interactive model analysis fromMiles and Hubernann.Based on the results of research drawn to conclusion: 1. The policy communications inmanaging village funds from the "transmission" dimension are quite good. Communication between village,BPD, and village community institutions in the planning and carrying out of village financeprograms/activities goes well through village meetings. The established village fund policy decisions are thencommunicated to village people. 2. The policy of communing in the implementation of village funds from the"clarity" dimension is also quite good. The decisions of the program/ activities financed by the village fundare clearly communicated to all parties involved in the planning and carrying out of the program/ activity,and to the village people. 3. The policy communications in managing village funds based on the "consistency"dimension are quite good. Policy decisions on well-funded village fund/activities are informed andimplemented fairly consistently by existing village governments BPD and public institutions.Key words: Communication Policy, Village Fund Administration.